PRIMARY AMENORRHEA IN AN ADOLESCENT FEMALE AS A PRESENTING FEATURE OF BOUCHER-NEUHÄUSER SYNDROME - Shah, Fatimah Zaherah Mohamed; Mohamed, Aimi Fadilah; Hafla, Sharifah Faradilla WM; Ghani, Rohana Abdul (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Primary amenorrhea has multiple aetiologies, encompassing disorders of ovaries, outflow-tract, pituitary/hypothalamus and genetic conditions. Hypogonadotropic hypogonadism refers to secondary hypogonadism due to deficiency in gonadotrophins, resulting in lack of estradiol stimulation, commonly due to pituitary or hypothalamus lesions, but can be due to genetic causes. CASE We describe a 16-year-old female who presented with primary amenorrhea and lack of secondary sexual characteristics, with no underlying medical conditions. Her sister and mother attained menarche at age 14. On examination, her BMI was 25 kg/m2 and height was 151 cm (mid-parental height 155 cm). She had no syndromic features, no anosmia, and no hirsutism or features of virilization, and no visual or neurological abnormalities. External genitalia was consistent with infantile labia with intact introitus. Tanner-staging for her breast was 2/5 and 1/5 for genitalia and pubic hair. Her hormonal profile showed hypogonadotropic hypogonadism, with undetectable estradiol (<36.7 pmol/L) and low gonadotrophin levels: Luteinizing-hormone 1.14 IU/L (2.4–12.6) and Follicular-stimulating-hormone 2.61 IU/L (3.5–12.5)]. Her bone age was delayed at 14 years, compared to a chronological age of 16. Karyotyping was 46,XX. Pelvic MRI showed hypoplastic uterus with normal vagina and ovaries. A pituitary MRI revealed a normal pituitary gland. Genetic testing confirmed 2 variants of PNPLA6 gene in keeping with Boucher-Neuhäuser syndrome CONCLUSION Boucher-Neuhäuser syndrome (BNS) is a rare genetic disorder characterized by cerebellar ataxia, chorioretinal dystrophy, and hypogonadism. We illustrate an interesting case presenting with isolated hypogonadotrophic hypogonadism with genetic screen suggestive of BNS, underlying the importance of considering genetic causes of primary amenorrhea even when presentation is in adolescence.